품종보호제도의 10년 운영평가와 중장기 발전방안 연구 - 성명환 (한국농촌경제연구원, 2009)
This study aims at finding out ways to strengthen the Plant Variety Protection which has been operated over the last 10 years by analyzing the protection system's operational results, effects on the local agricultural industry and practical issues presented during the period. The research proposes a mid and long-term development plan for the protect system based upon the analysis on overseas and domestic conditions, recent studies, operational conditions and outcomes of the system. Over the last 10 years of implementing the protection system, a consensus that the plant variety right is one of intellectual rights and needs to purchase by paying a proper price to use, has spread among producers. The introduction of the system has paved the way for reinforcing the competitiveness of domestic agricultural industry's cultivation of superior varieties. Increasing number of new plant varieties have been presented; Superior foreign varieties have been patented in Korea providing useful breeding materials. Public organizations have also played an important role in settling the system through various efforts to improve the breeding capacity, expand the investment in breeding and promote international cooperation as well as collaboration among universities, industry and government organizations domestically. As the perception of plant variety rights is increased and consumer rights are strengthened, the number of disputes concerning seeds has tended to rise steadily. However, there is inflexibility in approaching the process of resolving infringement issues in terms of accessibility, high costs and tedious time consuming. It is required for the protection granting agency to figure out ways to ensure a prompt and effective settlement protecting the rights of owners when an infringement issue occurs. In addition, there are problems in the actual operation of the system as well. Currently, a new plant variety can be protected by patent right, which is a type of intellectual property rights, as well as by the Laws for New Plant Variety Protection of the Seed Industry Law. Therefore, plant breeders have to undergo confusion and inconvenience of choosing one of those two systems which provide the same legal protection in principle. The government needs to provide an interceding method to resolve the problem. Although the procedure to apply for a patent or registration of a new variety has been simplified a lot, there are still unnecessary and cumbersome procedural requirements for an individual breeder to apply and register, and the terms used for the process are too complicated. Given the period of cultivation examination, which takes 1 to 1.5 years in general, the examining authority needs to consider a more speedy evaluation process reflecting the characteristics of each item. In addition, administrative ineffectiveness exists in managing the plant variety protection system because the operation agencies are different depending on the type of a plant. Korea Seed & Variety Service is an organization that is responsible for carrying out the entire process of variety examination and seed management. The organizations managing the works of protecting plant varieties need to be integrated into one institute so as to avoid duplicate works among organizations, firmly settle the protection system for entire plants and carry out an effective work of seed management. In order to ensure more improved variety protection, a dispute resolution system has to be established and take care of investigating infringement-related issues. For the question about the effects expected in the long run if the plant variety protection system is improved and firmly established, the biggest number of responders answered that the number of patents regarding variety protection would be increased, and it was followed by the opinions expecting that the intellectual property rights of breeders would be strengthened and the distribution order of plant varieties and seeds would be settled. Also, people believed that new demand for plant seeds would rise due to the expansion of seed exports. This study suggests building an information database and securing a patent reviewing system as methods to improve the patent and registration process for plant variety protection, and proposes separate roles of public and private sectors along with the direction to improve the support system for breeders. The methods to promote breeding in both sectors are provided as well. Furthermore, this research proposes the establishment of seed distribution order and registration system of seed name and the transfer of public management of government-supplied varieties to private sector.
Keywords: 품종보호; 종자관리